Smarandache Weak Subtraction Algebra: A. H. Handam - Team, Support (Thai Journal of Mathematics, 2013)
The notions of Smarandache weak subtraction algebra, Q-Smarandache ideals, prime Q-Smarandache ideals and weakly prime Q-Smarandache ideals are introduced. Some examples are given and several properties are investigated. Characterizations of ideals are provided. Different relations between Q-Smarandache ideals, prime Q-Smarandache ideals and weakly prime Q-Smarandache ideals are discussed.